“Fruitières comtoises” (Franche-Comté, France) - Alain Mélo (Revue de Géographie Alpine)
The first traces of breeders associated for merging together their milks to make marketable cheese (cooked pressed cheese) appear in the late Middle Ages (13th century). This entrepreneurial model really started to spread in the seventeenth century. But it was not before the 1880s that the whole production of Gruyère de Comté was organized. Co-operators created in the 1970s a “local production system” (système productif localisé), combining dairy farmers monitoring production through co-operatives, manufacturers and traders. Farmers, cheese co-operatives, traditional companies and businesses built a set of charters (Appellation d’Origine Protégée Comté, “campaign plans”, “contracts”). They developed a production system controlled by the stockbreeders in a defined territory which is one of the major components of this cheese-making industry. The mountain, defined as a geographic space, played an essential role in this long-lasting experience. The fruitière, as socio-economic form, emerged from the meeting between mountain (a geography), communities (people and their social rules) and feudalism (kind of power).